Pembuatan Nomor Induk Berusaha (NIB) Bagi UMKM Desa Branta Tinggi, Tlanakan, Pamekasan - Chairul Fajar Tafrilyanto; Septi Dariyatul Aini; Sri Indriati Hasanah; Kusyairi Kusyairi; Linda Susanti (Universitas Pendidikan Nasional, 2022)
The important role of MSMEs is increasingly being felt in the process of national economic development in Indonesia. Branta Tinggi Village is one of the villages in Tlanakan District, Pamekasan Regency which has a large number of MSMEs. However, there are still many MSME owners in Branta Tinggi Village who do not understand the importance of business legality in the form of making a Business Identification Number (NIB), because some people have an understanding that obtaining business permits and legality is a complicated and time-consuming matter. Meanwhile, the Business Identification Number (NIB) itself plays an important role in running a business. In carrying out this community service activity, the University of Madura KKN 4 Team is trying to increase the potential of MSMEs to improve the welfare of the people of Branta Tinggi Village. One of them is by helping to make NIB (Business Identification Number) in 3 hamlets. This community service activity is given in making a Business Identification Number (NIB) which is carried out through the door to door method where this service activity is carried out in real time by visiting the residence of each UMKM in three hamlets in the village of Branta Tinggi.